The expression 4 x b x b x b simplifies to 4b^3. This is because when you multiply the coefficients 4 and 1, you get 4. When you multiply the variables b, b, and b, you add the exponents, resulting in b^3. Therefore, 4 x b x b x b equals 4b^3.
A number a multiplied b times (so a x a is b=2, a x a x a is b=3, a x a x a x a is b = 4, and so on) is written as ab. Since 2 is multiplied 4 times, you have 24.
The correct simplification of the expression b^5 x b^4 is b^(5+4) which equals b^9. This is because when multiplying two terms with the same base, you add the exponents. In this case, b^5 x b^4 simplifies to b^(5+4) which is equal to b^9.
The result would be 12a2b.
4A = 5B. For finding the ratio A to B take B to the left side of the equation and 4 to the right side. 4 X A = 5 X B ( 4 multiplied by A = 5 multiplied by B) When any number goes to the other side you need to change the sign from + to - or / to X and vice versa. So when we take B to the left side it carries the / sign. Similarly with 4 ) A/B = 5/4 ( The ratio of A to B )
That is the value called the y intercept - value of y when x = 0 for example if y = 3x + 4 b = 4 and y = 4 when x = 0
Symmetry, which states that if A = B then B = A Put A = 4 and B = x + y
It is difficult to answer the question because it is still ambiguous. Putting brackets in helps. So: (3 over 4) x b = 3/4*b = 3*b / 4 YES but 3 over (4 x b) = 3/(4*b) is not 3/4*b
A number a multiplied b times (so a x a is b=2, a x a x a is b=3, a x a x a x a is b = 4, and so on) is written as ab. Since 2 is multiplied 4 times, you have 24.
A = (B x h)/2 As h is four times longer than B, we get h = 4 x B Then A = (B x 4B)/2 = (4 x B2)/2 = 2 x B2 thus B=sqrt(A/2) and h=4 x B=4 sqrt(A/2)
For example, (4.1076 x 10^3)/(2.8 x 10^4) = (4.1076/2.8) x [10 ^(3 - 4)] = 1.467 x 10^-1 or (4.1076 x 10^3)/(2.8 x 10^-4) = (4.1076/2.8) x [10 ^(3 - -4)] = 1.467 x 10^7
When you multiply 4x² by 4x², you multiply the coefficients (4 * 4 = 16) and add the exponents of the variables (x² * x² = x^(2+2) = x⁴). Therefore, the result is 16x⁴.
12b
Use x^a * x^b = x^(a+b). x^3 * x^4 = x^7
You can use the quadratic formula for an equation of the form a*x^2 + b*x + c = 0. x = (-b +/- sqrt(b^2-4*a*c))/(2*a) In this case: a = 1 b = -3 c = -28 x = (3 +/- sqrt(9 - 4*(-28)))/2 x = (3 +/- sqrt(121))/2 x = (3 +/- 11)/2 x = 7 or -4 Another option is to attempt to simplify the equation into the form (x-a)(x-b) = 0. Sometimes you can do this by observation. For example: 28 = 4*7 7-4 = 3 Thus: (x-7)(x+4)=0 In this case, a and b are known as the "roots" of the equation, with a = 7 and b = -4.
Base = 12 inchesArea = (b x h)/224 = (b x 4)/248 = b x 412 = b
If a = 2 and b = 2, then a + b = 2 + 2 = 4. Further, if a = 2 and b = 2, then a x b = 2 x 2 = 4. The answer is a and b are equal to 2.
13x